Severe Pulmonary Valvular Stenosis and Balloon Pulmonary Valvuloplasty (BPV): A Case Report - Nazrin, Tahera; Kabir, CM Shaheen; Nasrin, Sahela; Md Rokonujjaman, -; Huq, M Maksumul; Ali, Mohammad Liaquat; Karim, Md Rezaul (Ibrahim Cardiac Medical Journal, 2015)
Congenital pulmonary valve stenosis is a common congenital heart disease andIsolated pulmonary valve stenosis comprises 8-10% of all congenital heart disease. It is an acyanotic heart disease,but can present with severe cyanosis if it is associated with patent foramen ovale (PFO). Severe pulmonary stenosis with cyanosis can be misdiagnosed clinically. Proper evaluation and modern technique of treatment modality can save a life easily. We report a 5 years old boy with severe pulmonary valvular stenosis with PFO who was clinically misdiagnosed as a case of congenital cyanotic heart disease (Tetralogy of Fallot). After taking proper history, clinical examination and investigations we treated the baby by balloon pulmonary valvuloplasty (BPV) successfully without any complication. The short term (6 months) outcome of BPV showed excellent result. Ibrahim Cardiac Med J 2013; 3(1&2): 53-58